THE SIGNIFICANCE OF STORIES IN LEARNING FOREIGN LANGUAGES (Multidisciplinary Journal of Science and Technology, 2024)
The article explores the importance of stories in language learning and highlights how they can make the process more enjoyable, effective and inclusive. By integrating stories into language learning, students can achieve deeper and more intuitive proficiency in a new language, promoting both linguistic and cultural proficiency.